2017
DOI: 10.18006/2017.5(2).235.241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arbuscular mycorrhizal fungi (amf) on Camellia sinensis (L.) o. kuntze under greenhouse conditions

Abstract: KEYWORDS Arbuscular mycorrhizal fungi Camellia sinensis Consortium Inocula plant growth parameters ABSTRACTThe effects of arbuscular mycorrhizal fungi (AMF) on growth of tea both singly and in consortia were carried out in greenhouse environment for a period of 1 year. The effectiveness of native AMF species, viz., Acaulospora scrobiculata (A.s.), Glomus macrocarpum (G.m.), Rhizophagus intraradices (R.i.), on growth performance of C. sinensis plants were compared. The inoculating AMF noticeably increased the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
(19 reference statements)
2
9
0
Order By: Relevance
“…Many studies have reported that the application of AMF increased plant growth parameters [ 59 , 60 , 61 , 62 ]. Sharma and Kayang [ 63 ] reported that the application of AMF noticeably increased plant growth parameters of tea ( Camellia sinensis L.), such as the number of leaves, leaf area, plant height, shoot length, root length, and root and shoot weight. The combined application of biochar and AMF had a positive effect on the leaf number, leaf length, and shoot and root fresh and dry weights compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the application of AMF increased plant growth parameters [ 59 , 60 , 61 , 62 ]. Sharma and Kayang [ 63 ] reported that the application of AMF noticeably increased plant growth parameters of tea ( Camellia sinensis L.), such as the number of leaves, leaf area, plant height, shoot length, root length, and root and shoot weight. The combined application of biochar and AMF had a positive effect on the leaf number, leaf length, and shoot and root fresh and dry weights compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Tea (Camellia sinensis (L.) O. Kuntze) is an important commercial crop consumed worldwide, primarily as a beverage made from the processed leaves. Tea tree growth is often affected by soil nutrient levels, temperature, pruning, and soil microbes including arbuscular mycorrhizal fungi (AMF) (Burgess and Carr, 1996;Van Lelyveld et al, 1990;Sharma and Kayang, 2017). AMF effects on plant growth have been reported in many plants, including tea plants (Aliasgharzad et al, 2011;Shao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Sen et al [73] used A. nodosum (granule or liquid sprays) in field experiments with wheat in combination NPK fertilizers. The application of two liquid sprayings in combination with fertilizers increases in the grain and straw yields, respectively, compared to the control more than 10% [74][75][76][77][78][79][80]. Liquid spraying of the seaweed extract stimulates metabolic processes in the leaf and helps the plant exploit nutrients in the leaf.…”
Section: Discussionmentioning
confidence: 99%